2021
DOI: 10.1101/2021.03.12.435157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An extended DNA-free intranuclear compartment organizes centrosomal microtubules in Plasmodium falciparum

Abstract: Rapid proliferation of Plasmodium falciparum parasites in human red blood cells is the cause of malaria and is underpinned by an unconventional cell division mode, called schizogony. Contrary to model organisms, P. falciparum replicates by multiple rounds of closed and asynchronous nuclear divisions that are not interrupted by cytokinesis. Organization and dynamics of the critical nuclear division factors are, however, poorly understood. Centriolar plaques, the centrosomes of P. falciparum, are important regul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…1C-E). On the nuclear side this might correspond to the future acentriolar plaques that stain negative for DNA, as observed in asexual blood stages [14]. Upon transition to stage V, the microtubule network progressively disassembled and the tips sequentially became more rounded.…”
Section: U-exm Of Developing P Falciparum Gametocytes Highlights the Subpellicular Microtubule Networkmentioning
confidence: 88%
See 2 more Smart Citations
“…1C-E). On the nuclear side this might correspond to the future acentriolar plaques that stain negative for DNA, as observed in asexual blood stages [14]. Upon transition to stage V, the microtubule network progressively disassembled and the tips sequentially became more rounded.…”
Section: U-exm Of Developing P Falciparum Gametocytes Highlights the Subpellicular Microtubule Networkmentioning
confidence: 88%
“…The structural organisation of the acentriolar plaque has recently been refined in asexually replicating blood stages [14,41] that undergo endomitosis but without axoneme nucleation. In these stages, the acentriolar plaque also shows a bipartite organisation with an extranuclear region containing centrin that is linked through a nuclear pore to an intranuclear chromatin-free region harbouring microtubule nucleation sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A factor that more overtly limits nuclear number is the centrosome (Arnot et al, 2011). Each round of division precludes centrosome duplication to form the poles between which chromosomes will be segregated (Simon et al, 2021). Transient localization of the aurora kinase PfArk1 to the centrosome just prior to its duplication has been described (Reininger et al, 2011).…”
Section: Final Number Of Merozoites Could Be Predefined By a Counting Mechanismmentioning
confidence: 99%
“…However, recent insights from UExM has revealed that the CP is in fact extranuclear, and is not embedded in the nuclear envelope at any point during mitosis. UExM, STED microscopy, and correlative light electron microscopy (CLEM) has further revealed that nucleation of microtubules resides within a chromatin free subcompartment within the nucleus, distal to the location of Centrin, a CP component, and proximal to a nuclear pore marker (Nup313) (Simon et al, 2021). This study has clearly established that whereas the CP is at the poles of the mitotic spindle, the CP is extranuclear, and MT nucleation capacity resides at a protein-dense region internal to the nucleus, but devoid of chromatin (Fig.…”
Section: Nuclear Division Organization By Mtocs Of T Gondii and Plasmodium: Structural And Functional Insightmentioning
confidence: 99%